The Development of Products with Personality and Co-Created Products - Teodora-Iustina TUDOR; Nicolae IONESCU (Communications of International Proceedings, 2020)
The purpose of this paper is to assess the importance of co-created products and products with personality and people's reaction to them. In a world in which people want to stand out and be unique, this kind of products gain increasing importance by eliciting emotions and pleasant feelings. Thus, strong bonds are created between users and these types of products, and some of them end up being preserved long after they are unable to fulfil their primary functions. Products with personality and co-created products will become the future of design, because people have a growing desire to be surprised and intrigued.
Keywords: Product with Personality; Co-Created Products; Design; Emotions.